Chinese Medicine Formula Kai-Xin-San Ameliorates Neuronal Inflammation of CUMS-Induced Depression-like Mice and Reduces the Expressions of Inflammatory Factors via Inhibiting TLR4/IKK/NF-κB Pathways on BV2 Cells - Qu, Suchen; Liu, Mengqiu; Cao, Cheng; Wei, Chongqi; Meng, Xue-Er; Lou, Qianyin; Wang, Bin; Li, Xuan; She, Yuyan; Wang, Qingqing; Song, Zhichao; Han, Zhengxiang; et al. (Frontiers in Pharmacology, 2021)
Kai-Xin-San (KXS) is a traditional Chinese medicinal formula composed of Ginseng Radix et Rhizoma, Polygalae Radix, Acori Tatarinowii Rhizoma, and Poria for relieving major depressive disorder and Alzheimer’s disease in traditional Chinese medicine (TCM) clinics. Previous studies on the antidepressant mechanism of KXS mainly focused on neurotransmitter and neurotrophic factor regulation, but few reports exist on neuronal inflammation regulation. In the current study, we found that KXS extracts exerted antidepressant effects in chronic unpredictable mild stress-induced depression-like mice according to the results of behavioral tests. Meanwhile, KXS extracts also inhibited the activation of microglia and significantly reduced the expressions of inflammatory cytokines such as IL-1IL-andF-in the hippocampus of miceIn mice BV2 microglia cell lines, KXS extracts reduced the expressions of pro-inflammatory factors in BV2 cells induced by lipopolysaccharide via inhibiting TLR4/IKK/NF-κB pathways, which was also validated by the treatment of signaling pathway inhibitors such as TAK-242 and JSH-23. These data implied that the regulation of pro-inflammatory cytokines in microglia might account for the antidepressant effect of KXS, thereby providing more scientific information for the development of KXS as an alternative therapy for major depressive disorder.